The effects of the Red 003 Fire on woodland caribou (Rangifer tarandus caribou) habitat in the Sydney Range - Silva, Joseph
Disturbances, including forest fires, are considered a primary driver of population decline in boreal woodland caribou populations across Canada. The Sydney Range in northwestern Ontario has been assessed as not self-sustaining due to a low population estimate and extensive anthropogenic and natural disturbances. In 2016, the Red 003 Fire burned most of the northwest corner of the Sydney Range, which contained the highest habitat value and likelihood of occupancy for the Sydney caribou. Managers are concerned the Red 003 Fire could cause decline in the Sydney caribou population. Telemetry data was used to create a set of models in a Resource Selection Function to explain how caribou used habitat prior to the Red 003 Fire. The telemetry data indicated the importance of the area that burned in the Red 003 Fire as winter habitat for the Sydney caribou. The Resource Selection Function indicated that caribou displayed differing levels of avoidance of recent burns across seasons. Due to the large size of the Red 003 burn and the high percentage of post-fire residuals, it is likely caribou will continue to use habitat within and around the Red 003 burn. However, the persistence of the Sydney caribou population likely hinges on the ability of remaining suitable habitat and the regenerating habitat in 1980s burns to compensate for the areas affected by the Red 003 Fire.